Research of durability of toothed connection is on static bend - Koval, Lyubomyr (Forestry, Forest, Paper and Woodworking Industry, 2024)
In the article the results of research of durability of toothed connections of thorns are resulted at a static bend and optimization of object of researches is conducted.